(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The aim of this study is to study the possibilities of obtaining materials with a material shift to the higher wavelengths that fall within the C-Band window currently used in fiber optic communication systems. This is done by mixing pure SiO2 with different materials and different percentages. We find the evidence of refraction of the core material in an optical fiber and study the change of these clues by sequential wavelength of light from the solimer constants obtained from the OptiFiber program. We then calculated the physical dispersion factor DM for each of the studied materials by writing a special matlab program for this study and thus studying the change in the physical dispersion of these materials by the sequential wave length.